Penindakan Hukum terhadap Praktik Penimbunan Bahan Bakar Minyak (BBM) Subsidi di Wilayah Polres Batu Bara Berdasarkan Undang-Undang Nomor 22 Tahun 2001 dan Undang-Undang Nomor 7 Tahun 2014 - Ryan Seftiansyah; Tri Reni Novita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The practice of hoarding subsidized fuel oil (BBM) in the Batu Bara Police jurisdiction has increased significantly by 667% over a five-year period (2020-2024), with total estimated state losses reaching Rp1.087 billion. This condition is exacerbated by the geographical location of Batu Bara Regency which borders directly with the Malacca Strait, creating potential for smuggling subsidized fuel to neighboring countries. This study aims to analyze the legal enforcement against subsidized fuel hoarding practices in the Batu Bara Police jurisdiction based on Law Number 22 of 2001 concerning Oil and Natural Gas and Law Number 7 of 2014 concerning Trade. This research uses normative-empirical legal method with a qualitative approach. Data analysis was conducted qualitatively using grammatical, systematic, and teleological interpretations. The results show that the Batu Bara Police uses Article 55 of Law Number 22 of 2001 as the primary legal basis because it is lex specialis, while Article 107 of Law Number 7 of 2014 is applied as a subsidiary legal basis in layered indictment constructions. The application of both laws faces obstacles such as high rates of case file returns (P-19), difficulties in proving the subjective elements of the offense, and inconsistent perceptions between investigators and prosecutors regarding the appropriate indictment construction. Factors affecting enforcement effectiveness are multidimensional, including normative factors (inconsistency between the two laws), institutional factors (limited technical capacity of investigators and weak inter-agency coordination.